Use of information technology in the segment of honey technology in public schools in the municipality of Tenente Laurentino Cruz/RN (Research, Society and Development, 2023)
The aim of this project was to raise awareness and disseminate information about the social, economic and environmental importance of bees (Apis mellifera), making people understand the importance and necessity of bees and seeking to publicize and value bee products. This work aimed to reach public school students, farmers and beekeepers in the municipality of Tenente Laurentino Cruz/RN, as well as expanding it to the virtual public, through digital platforms (Instagram and TikTok). When applied, it enabled interaction between the students involved in these activities and the school community visited, invited beekeepers and beekeepers and the public reached by the digital platforms used. The main objective was to raise awareness, increase the positive perception of bees and value them. In the first school, the presentation was attended by 60 students from classes 6, 7 and 8 of primary school, 6 teachers and 1 beekeeper from the community. In the second school, 41 students from classes 1, 2, 3, 3, 4 and 9 of primary school, 9 teachers and 1 local beekeeper attended the presentation. Therefore, it can be concluded that this project has successfully achieved most of its objectives, since the dissemination of beekeeping knowledge through digital platforms, with a total of 2,700 users, and visits to schools to give talks, had a positive return, reaching 101 students, 15 teachers and 2 beekeepers.